Video tempering detection assessment in full reference mode using difference matrices. (19th May 2019) - Sharma, Gajanand; Goyal, Dinesh
Abstract: Frequent availability of low-speed internet connections together with easy availability of video capturing in the form of low-cost cameras and digital camcorders, and free video editing software running on low-cost machines, creates the possibility of real vulnerability in the video. To make improvements to images and videos, it is becoming easier for ordinary people to use malicious purposes to access digital doctor tools. This means that television, such as videos and videos on YouTube's popular Internet websites that have been shown to be images and videos, have been scattered and their honesty cannot always be allowed. On this paper, a video tempering detection technique is proposed under the entire reference scheme. This means that the original video file is compared to the analysis activity. The proposed project uses a general data structure which is called the difference matrix which is used as a purpose. The proposed project takes steps without traditional comparison because it indicates that video edits are made to include objects or it is simply a result of video brightness and contrast enhancement.